Strategies for Recruiting People With Dementia to Music Therapy Studies: Systematic Review. (26th June 2021) - Baker, Felicity A; Pool, Jonathan; Johansson, Kjersti; Wosch, Thomas; Bukowska, Anna A; Kulis, Aleksandra; Blauth, Laura; Stensæth, Karette; Clark, Imogen N; Odell-Miller, Helen
Abstract: Positive effects of music therapy for people with dementia and their family carers are reported in a growing number of studies. However, small sample sizes or low recruitment rates often limit the success of these research studies. More adequately powered evidence-based studies are needed to impact policy and funding in dementia care. This systematic review examined recruitment strategies in music therapy clinical trials involving people living with dementia and/or their family carers. Eligible studies described enrolment, consent, accrual, or recruitment methods as well as recruitment or consent rates. Thirty studies with a total of 1, 192 participants were included. Recruitment and conversion rates in residential aged care facilities (RACFs) (14 studies) were substantially higher than in community-based studies (16 studies). Whereas studies in RACFs most commonly recruited participants through staff approaching residents face-to-face or conversing with residents' legal guardians, community-based studies utilized a vast array of strategies, including staff referral, demonstrations/information sessions by researchers, advertisements, and direct contact with residents. Recruitment rates are likely to be higher when recruiters have an existing relationship with potential participants and when an independent third-party dementia organization is involved. Randomized controlled trials led to equally or greater recruitment conversion rates than other designs. Findings suggest that recruitment in dementia trials is complex, challenging, and needs thorough planning and consideration to be time- and cost-effective. Future studies should include reporting of recruitment strategies, enrolment rates, and related aspects so that researchers can better design recruitment strategies and estimate resources needed to reach the target sample size.